Efektivitas Penggunaan Media Boneka Tangan Terhadap Keterampilan Bercerita Siswa Kelas V Sekolah Dasar - Rahmatilah, Farihatul; Supratno, Haris; Asmarani, Ratih (IJPSE : Indonesian Journal of Primary Science Education, 2021)
The use of instructional media is a creative learning activity that students enjoy doing. The purpose of this study is to describe (1) the learning process of using hand puppet media of storytelling skills, (2) student responses on learning using hand puppet media, (3) the result of storytelling skills by using hand puppet media. The research is a qualitative and quantitative research design. Qualitative design is emphasizing more attention on a "process". For quantitative design is to determine the average value before and after learning. The sources are teachers, students, list of student names, the assessment results before implementation, class teacher identity, school profiles, lesson plans, syllabus, and theme books. The subjects are teachers and students, and the object is hand puppet media. The results showed that by using hand puppet media on storytelling at first and second meetings shows learning process runs effectively and is accordance with the teacher’s plan.. The results of questionnaire concluded a good response with an average score of 94.9%. The data from pre-test scores on learning I achieves 61.62. While the average score after learning process (post test) is 78.10. Through comparison of the average score on pre-test and post-test is increased by 16.48. Then, the data from post test scores on learning II is 80. Through comparison of the score at the first and second meeting is increased by 1.9. Based on the results, it can be concluded that hand puppet media can be used as an appropriate source of learning for storytelling skills in elementary schools.